Rational Economic Agents as Formal Logical Systems - Paolo Gentilini; Corrado Benassi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
We describe economic agents as formal logical systems of the first order, and then able to show that for any ordinary geometric description of an agent as a preordering over a given choice set within the set of reals, there exists a corresponding logical description in the space of the first order-formal systems, and vicevesa. This approach allows to distinguish formally among propositions known to economic agents and propositions concerning them. Also, we show that for any finite commodity space one can build consistent agents as first-order formal systems, and hence an economy defined as a collection of such systems, both of which can be mapped into the standard topological framework.
Keywords: 330